Expression of the Intracellular COPT3-Mediated Cu Transport Is Temporally Regulated by the TCP16 Transcription Factor - Andrés-Colás, Nuria; Carrió-Seguí, Angela; Abdel-Ghany, Salah E.; Pilon, Marinus; Peñarrubia, Lola (Frontiers in Plant Science, 2018)
Copper is an essential element in plants. When scarce, copper is acquired from extracellular environment or remobilized from intracellular sites, through members of the high affinity copper transporters family COPT located at the plasma membrane and internal membrane, respectively. Here we show that COPT3 is an intracellular copper transporter, located at a compartment of the secretory pathway, that is mainly expressed in pollen grains and vascular bundles. Contrary to the COPT1 plasma membrane member, the expression of the internal COPT3 membrane transporter was higher at 12 hours than at 0 hours of a neutral photoperiod day under copper deficiency. The screening of a library of conditionally overexpressed transcription factors implicated members of the TCP family in the COPT3 differential temporal expression pattern. Particularly, in vitro, TCP16 was found to bind to the COPT3 promoter and down-regulated its expression. Accordingly, TCP16 was mainly expressed at 0 hours under copper deficiency and induced at 12 h by copper excess. Moreover, TCP16 overexpression resulted in increased sensitivity to copper deficiency, whereas the tcp16 mutant was sensitive to copper excess. Both copper content and the expression of particular copper status markers were altered in plants with modified levels of TCP16. Consistent with TCP16 affecting pollen development, the lack of COPT3 function led to altered pollen morphology. Furthermore, analysis of copt3 and COPT3 overexpressing plants revealed that COPT3 function exerted a negative effect on TCP16 expression. Taken together, these results suggest a differential daily regulation of copper uptake depending on the external and internal copper pools, in which TCP16 inhibits copper remobilization at dawn through repression of intracellular transporters.